Evaluation of Synchronization and MPPT algorithms in a DFIG Wind Turbine Controlled by an Indirect Matrix Converter - Ahmad Khajeh; Reza Ghazi; Mohamad Hosseini Abardeh; Mahmoud Oukati Sadegh (Institute of Advanced Engineering and Science, 2018)
Most of generators utilized in wind turbines are the Doubly-Fed Induction Generator (DFIG). Indirect matrix converter (IMC) is a candidate for substituting the traditional back-to-back converter in the future due to advantages gained by elimination of electrolytic capacitor. Starting DFIG wind turbines and synchronizing to the grid is a challenge in practice because of large inrush currents that could damage switches. Synchronizing the DFIG wind turbine controlled by the IMC is presented in this paper. Also, maximum power point tracking algorithm performance of this configuration is examined. A laboratory scale prototype of the proposed configuration is built. Experimental results have confirmed effectiveness of this configuration.